Seed Development and Maturation of Eryngo (Eryngium foetidum L.) - Boonsong Ekpong,; Sutevee Sukprakarn, (Agriculture and Natural Resources, 2006)
Flowering pattern and seed development were studied in two eryngo accessions (EF006 and EF007) to determine the optimum time of harvest for seed production. Flowering peak was 117 days after transplanting (35.6 umbel heads) and 121 days after transplanting (38.7 umbel heads) in EF006 and EF007 accessions, respectively. Seed in both accessions reached their physiological maturity 40 days after anthesis, with 93.75-95.75% germination when the seed head had just begun to turn brownish black in color. Shattering, however, commenced 65 days after anthesis.